Unravelling Receptive Language Acquisition: A Comprehensive Study of Deaf Students' English Language Acquisition - Safira Ramadhani, Risa; Hufad, Achmad (Angstrom Centre of Education, 2024)
This study aims to explore in-depth understanding of receptive language acquisition and English language acquisition of deaf students. The focus of the research is on the aspects of receptive language acquisition and English language acquisition of deaf students. This research uses the literature analysis method which involves the study of scientific articles, research reports, and other related literature at the national and international levels that relate to the receptive language acquisition and English language acquisition of deaf students. The data was analysed qualitatively with a descriptive approach. The findings of this study are that deaf children have great potential, despite facing barriers in language acquisition. they tend to have a visual learning type, and the use of various learning media can help improve language acquisition. A total communication approach, which involves multiple forms of communication, can help in deaf children's first language acquisition. In addition, factors such as the degree of deafness, hearing aid use, and family background also affect their language development. In foreign language learning, the use of national sign language and effective learning strategies can help deaf students overcome difficulties. And the importance of co-operation between teachers, students, parents and the learning environment is crucial in helping deaf children overcome their language challenges.